The migration-traffiking nexus : an investigation into the survival strategies of the Philippines' poorest migrants : a thesis presented in partial fulfilment of the requirements for the degree of Masters of International Development, Massey University, New Zealand - West, Christey (Massey University, 2014)
The Philippines’ social and economic complexities limit the life choices of its people and migration has become the only perceived method to achieve upward social and economic mobility. Filipinos are being ‘groomed’ to migrate as a ‘culture of migration’ has become ingrained in the national psyche, creating a desperation to migrate which makes the poorest Filipinos prime targets for human traffickers. The aim of this research project was to investigate the driving factors behind the culture of migration of the Philippines and the implications for trafficking. Underpinned by a qualitative methodology, fieldwork was conducted over five months in Manila and Samar Island in the Philippines. The findings of this study show that poverty and inequality form the context which forces Filipinos to leave their hometown and the factors which make them vulnerable to trafficking are correlated with endemic corruption and the resulting lack of law enforcement. Additionally the findings revealed that recruitment practices which exploit migrants, including the betrayal of neighbours and kin, have become common practices leading to people being trafficked in poor villages. When trafficking survivors are repatriated they often find the same constraints persist. Hence they are left with no choice but to migrate again and risk being re-trafficked. This thesis concludes that the vulnerabilities inherent in poverty are exacerbated by a complex culture of migration which makes poor Filipinos desperate to accept any offer to migrate and, thus, exposes them to human traffickers.
Keywords: Poverty, Philippines; Human trafficking, Philippines; Migrants, Philippines; Filipino employment